MISTERI BAHASA LIDAH: SINTESIS TEOLOGIS TENTANG KARUNIA ROH, BAHASA DOA, BAHASA KOMUNIKASI DAN TANDA ESKATOLOGIS - Ibrahim, Ibrahim (STT KINGDOM BALI, 2026)
The phenomenon of tongues (glossolalia) has been one of the most important gifts of the Holy Spirit discussed since the time of Pentecost (Acts 2). The Pentecostal and Charismatic traditions see it as a sign of the outpouring of the Spirit, while the mainstream church sees it more as one of the gifts among many others. This article aims to present a theological synthesis of the four main dimensions of language: (1) as the gift of the Holy Spirit that bestows on the body of Christ; (2) as a language of prayer that deepens one's personal relationship with God; (3) as a language of communication to spread the gospel across languages; and (4) as an eschatological sign that indicates the fulfillment of God's promises. This study uses qualitative methods based on literature studies and biblical-theological analysis. The results of this study confirm that glossolalia is a multidimensional pneumatological phenomenon that must be practiced in an orderly, mature manner, oriented towards the development of the body of Christ and the mission of God, so that the church avoids reducing or absolutizing it.